2018
DOI: 10.7717/peerj.4626
|View full text |Cite
|
Sign up to set email alerts
|

Surface display for metabolic engineering of industrially important acetic acid bacteria

Abstract: Acetic acid bacteria have unique metabolic characteristics that suit them for a variety of biotechnological applications. They possess an arsenal of membrane-bound dehydrogenases in the periplasmic space that are capable of regiospecific and enantioselective partial oxidations of sugars, alcohols, and polyols. The resulting products are deposited directly into the medium where they are easily recovered for use as pharmaceutical precursors, industrial chemicals, food additives, and consumer products. Expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…As mentioned previously, a few strong G. oxydans promoters have been reported (Hu et al, 2015;Li et al, 2016;Blank and Schweiger, 2018). To verify the strength of our strongest screened promoters, we also obtained four reported strong promoters (P tufB , P dnak , P hp0169 , and P 264 ) from the genomes of WSH-003 and ATCC 621H.…”
Section: Evaluation Of Promoter Strength By Measuring Mcherry Expressionmentioning
confidence: 72%
See 1 more Smart Citation
“…As mentioned previously, a few strong G. oxydans promoters have been reported (Hu et al, 2015;Li et al, 2016;Blank and Schweiger, 2018). To verify the strength of our strongest screened promoters, we also obtained four reported strong promoters (P tufB , P dnak , P hp0169 , and P 264 ) from the genomes of WSH-003 and ATCC 621H.…”
Section: Evaluation Of Promoter Strength By Measuring Mcherry Expressionmentioning
confidence: 72%
“…Though some progress were achieved in promoter discovery, it was hard to apply the promoters to other metabolic pathways because the promoters were relatively weak without systematic comparison. Saito et al, found some strong promoters of G. oxydans, such as P tufB , P 0169 , and P 264 (Saito et al, 1997;Yuan et al, 2016;Blank and Schweiger, 2018). Moreover, Kallnik and Hu reported some promoters of different strengths in G. oxydans (Kallnik et al, 2010;Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the CCD was employed to investigate the interactions between the significant variables and determine their optimum values for riboflavin production. A total of 30 experimental combinations for four significant variables (fructose, tryptone, K 2 HPO 4 , and CaCl 2 ) were achieved at five levels with the center points replicated six times in the experiment (run order: 4,18,20,22,23,29). The range of variables concentrations at different coded levels shown in Table 7.…”
Section: Genome Features and Identification Of Riboflavin In The G Omentioning
confidence: 99%